(untitled) (Bangladesh Rice Journal, 2019)
The assessment of genetic diversity among nineteen maintainer lines was studied based on thirteen qualitative traits. The single linkage clustering, morphological dendogram were performed to assess the traits. Most of the traits showed variation in different maintainer lines except auricle colour. On the basis of flag leaf attitude, a maximum four groups were formed with erect, semi-erect, horizontal and descending type leaf angle. The maintainer line BRRI20B has awn tip, which is unique from the rest of the studied maintainer lines. Nineteen maintainer lines were grouped into four different clusters and a considerable level of variability was displayed for most of the traits examined. The clustering pattern revealed, cluster I was the largest and consisted seven maintainer lines. Among them maintainer lines BRRI52B and BRRI60B were the most closely associated. Cluster II represent diverse sources materials and its revealed non-correspondence of geographic diversity with genetic divergence. Thus the cluster analysis has revealed the genetic variation and the traits contributing for the variation. Hence, this maintainer lines can be utilized for trait improvement in breeding programmes for the traits contributing for major variation. Bangladesh Rice j. 2018, 22(2): 79-87